PRESERVING AND MANAGING CHINESE SETTLEMENT HERITAGE TOURISM IN LASEM, INDONESIA - Prisca Kiki WULANDARI; Muhammad BAIQUNI; Ahmad ZUBAIDI (Geo Journal of Tourism and Geosites)
This research examines Chinese settlements' preservation and management strategies as heritage tourism in Lasem, Rembang, Indonesia. Ancient houses in Chinatown settlements are vulnerable and require a social resilience strategy as a solution. This study used a qualitative approach and data collection techniques through observation, in-depth interviews, documentation, and focus group discussion (FGD). The informants were owners of ancient houses utilizing their buildings as heritage tourism destinations. The results of this study show that the community or owner in managing settlements or Chinese houses as tourist destinations should have three capacities in the social resilience perspective, namely 1) coping capacity, which includes resources, knowledge, skills, and learning; community as the main actor, community awareness, and social kinship system; 2) adaptive capacity which includes: community networks, human and environmental relations, and community participation; and 3) transformative capacity which includes community infrastructure, multi-stakeholder partnerships, technological innovation, diversity and economic innovation. This study concludes that the owners of ancient houses in Chinatown settlements who utilize their buildings as tourism destinations are quite resilient.